Trend for Risk Covid-19: A Case Study in Indonesia - Ilmi, Laili Rahmatul; Praptana, Praptana (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Since the end of 2019, the whole world has been shocked by the increasing outbreak of Covid-19 including in Indonesia. Google trend data provides important information that supports decision making. The aims of this study for measuring the activities of cyber users to get the latest information regarding the spread of Covid-19, the use of masks, the importance of maintaining personal hygiene, lockdown, environmental cleanliness, and being able to predict an increase or decrease in Covid-19 cases. This study explores data using google trends to reduce the number of Indonesian citizens’ anxiety in the Covid-19 case. the data was analysis using stata for Time-Lag Correlation. Relative search volume (RSV) by using Google Heat Map. The correlation test RSV between Covid-19 cases and the use and price of masks, hand washing and, number of cases Covid-19. the test shows that the value of F (2, 242). The variables tested were 2 variables, namely the use of masks and washing hands while the observed number was 242. The R-Squared value showed 0.1163 that all independent variables had an effect on the dependent variable.